Pemanfaatan Pati Biji Durian (Durio zibenthinus murr) Menjadi Edible Film Menggunakan Plastisizer Polietilen Glikol (PEG) - Fijri, Annisa Nurul; Dewata, Indang (Jurnal Kependudukan dan Pembangunan Lingkungan, 2022)
The edible film is a bioplastic in the form of a thin layer that can be decomposed with the help of microorganisms. This study aims to determine the effect of adding chitosan to the edible film of durian seed starch on the mechanical properties and structure of the edible film. This research was conducted by varying the concentration of chitosan at concentrations of 0%, 0.5%, 1%, 1.5%, and 2%. The resulting edible films were analyzed for tensile strength, elasticity, and characterization using Thermogravimetric Analysis (TGA). The optimum tensile strength obtained with the addition of 1% chitosan is 1.414 Mpa. The maximum elasticity value obtained in the edible film with the addition of 1% chitosan is 436.2 Mpa. The thermal resistance of the film will be higher as the tensile strength increases. The film begins to decompose at 250 ºC and ends at 500 ºC.